Mainstreaming women in development? : a gender analysis of the United Nations Development Programme in South Africa. - Rippenaar-Joseph, Trunette (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Political Science))--University of Stellenbosch, 2009.